13.2k views
5 votes
Drag steps in the given order to evaluate this expression. (−3)(2)−7(−3)−10

User Dyo
by
6.4k points

2 Answers

3 votes
Step 1:
Multiply the numbers in parentheses:
(-3 * 2) - (7 * (- 3)) - 10
-6 - (- 21) -10
Step 2:
Equal signs are added:
-6 + 21-10
Step 3:
Make the algebraic sum:
-6 + 21-10 = 5
Answer:
the final result is 5.
User Derryck
by
5.9k points
7 votes

Answer:


(-3)(2) - 7 ( -3) -10\\= (-6) - (-21) -10\\= -16 + 21 - 10\\= -5\\

Explanation:

We will follow the rule of BODMAS

B - Bracket Of

D - Division

M = Multiplication

A = Addition

S = Subtraction

On solving the give equation as per the order of BODMAS, we get -


(-3)(2) - 7 ( -3) -10\\= (-6) - (-21) -10\\= -16 + 21 - 10\\= -5\\

User HexAndBugs
by
6.3k points